2021
DOI: 10.1371/journal.pone.0256482
|View full text |Cite
|
Sign up to set email alerts
|

Original antigenic sin responses to Betacoronavirus spike proteins are observed in a mouse model, but are not apparent in children following SARS-CoV-2 infection

Abstract: Background The effects of pre-existing endemic human coronavirus (HCoV) immunity on SARS-CoV-2 serologic and clinical responses are incompletely understood. Objectives We sought to determine the effects of prior exposure to HCoV Betacoronavirus HKU1 spike protein on serologic responses to SARS-CoV-2 spike protein after intramuscular administration in mice. We also sought to understand the baseline seroprevalence of HKU1 spike antibodies in healthy children and to measure their correlation with SARS-CoV-2 bin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Recently, we observed anti-S2 cross-reactivity in naive older children but not in the younger children (<4 years old), who share homology with HKU1, 229E, and OC43 23 , 24 . OAS was also observed in mice immunization studies with seasonal CoV followed by SARS-CoV-2 spike 25 . Most of these cross-reactive antibodies do not neutralize SARS-CoV-2, as was observed with samples from 10 children with seasonal CoVs in our study.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, we observed anti-S2 cross-reactivity in naive older children but not in the younger children (<4 years old), who share homology with HKU1, 229E, and OC43 23 , 24 . OAS was also observed in mice immunization studies with seasonal CoV followed by SARS-CoV-2 spike 25 . Most of these cross-reactive antibodies do not neutralize SARS-CoV-2, as was observed with samples from 10 children with seasonal CoVs in our study.…”
Section: Discussionmentioning
confidence: 72%
“…The original antigenic sin hypothesis suggests that preexisting immunity results in the reactivation of a response to an earlier strain, as opposed to the formation of an unbiased response against the current strain. While this recall could offer temporal advantages, it may reduce the formation of neutralizing antibodies, thereby dampening effective clearance of the novel virus, as has recently been reported in mouse models ( Lapp et al, 2021 ; Lin et al, 2022 ). Seminal studies of responses to influenza, based on epidemiology, modeling, and repertoire profiling, suggest that the antibodies generated from childhood exposure to influenza are ‘imprinted’ and exert a major influence on the nature of the antibody response elicited upon subsequent exposures in humans ( Francis et al, 1947 ; Fonville et al, 2014 ; Kucharski et al, 2015 ; Gostic et al, 2016 ; Lee et al, 2019 ).…”
Section: Discussionmentioning
confidence: 97%
“…To this end, the relationship between ADE and COVID-19 has been assessed (Lee et al, 2020). However, recent reports demonstrated that, although similar phenomena have been observed in mice, stronger evidence is required to confirm whether ADE and original antigenic sin can affect vaccination and human resistance against the virus (Lapp et al, 2021;Vashishtha, 2021).…”
Section: Discussionmentioning
confidence: 99%